2010
DOI: 10.1111/j.1748-5967.2010.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) in tomato fields and its relationship to weather factors

Abstract: A survey was conducted in tomato fields at different localities to assess the distribution of tomato fruitworm Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) in Punjab Province, Pakistan. The effect of weather factors on its population was also investigated. Eleven tomato‐growing districts were selected and data for larval population and fruit infestation were recorded. The maximum larval population (5.2 larvae/plant) of H. armigera was recorded in Bahawalpur district with 32.6% fruit infestation. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Relationship between Weather Parameters and Incidence of Gram Pod Borer, Helicoverpa armigera on Chickpea of Pandey et al (2012) and Sharma et al (2012) they recorded negative non-significant correlation between larval population and relative humidity. Umbarkar et al (2010), Wakil et al (2010) and Mahawar et al (2015) computed negative significant positive correlation with larval population and relative humidity; these findings are also supports present findings.…”
Section: Regression Analysis Between Larval Population Of H Armigera ...supporting
confidence: 90%
“…Relationship between Weather Parameters and Incidence of Gram Pod Borer, Helicoverpa armigera on Chickpea of Pandey et al (2012) and Sharma et al (2012) they recorded negative non-significant correlation between larval population and relative humidity. Umbarkar et al (2010), Wakil et al (2010) and Mahawar et al (2015) computed negative significant positive correlation with larval population and relative humidity; these findings are also supports present findings.…”
Section: Regression Analysis Between Larval Population Of H Armigera ...supporting
confidence: 90%
“…elicoverpa armigera Hübner (Lepidoptera: Noctuidae), a major polyphagous insect pest of many crops (Marzban et al, 2009), has a wide geographical range, mobility, migratory potential, facultative diapause, high fecundity and a great tendency to develop resistance against insecticides, key factors that determine its importance as insect pest (Fitt, 1989;Zalucki, 1991;Wakil et al, 2009a;2009b;2010). Excessive use of synthetic insecticides worldwide warrants environmental and human health concerns, and urges researchers to develop safer alternatives for eco-friendly pest management (Cherry et al, 1997).…”
mentioning
confidence: 99%
“…Maximum and minimum temperature and maximum relative humidity did not show any significant correlation. Wakil et al (2010) has reported that temperature was positively correlated. While, relative humidity showed negative interaction with the larval and fruit infestation.…”
Section: Resultsmentioning
confidence: 99%